Public Diplomacy In Establishing Harmonious Relations Between Indonesia And Malaysia (Case Study Of Public Diplomacy On The Malaysian Claims Indonesian Culture) - Elly Yuliawati, Elly Yuliawati (2015)
This study aimed to find out the public diplomacy understanding in establishing harmonious relations between Indonesia and Malaysia, based on the experience and society subjective motives which are categorized into the executive, legislative, and community (include academicians, cultures and media) both from Indonesia and Malaysia. In detailed the research analysis, the researcher used naturalistic interpretive method. The selection of informants was done by using purposive sampling. The research data were collected through interviews, observation and documentation studies. The data collected is then analyzed based on intersubjective agreement and its validity tested through confirmation, credibility and depth discussion.